2008
DOI: 10.1007/s00427-008-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of nervous systems to metamorphosis in feeding and non-feeding echinoid larvae, the transition from bilateral to radial symmetry

Abstract: The development of nervous system (NS) in the non-feeding vestibula larva of the sea urchin, Holopneustes purpurescens, and the feeding echinopluteus larva of Hemicentrotus pulcherrimus was examined by focusing on fate during metamorphosis. In H. purpurescens, the serotonergic NS (SerNS) appeared simultaneously and independently in larval tissue and adult rudiment, respectively, from 3-day post-fertilization. In 4-day vestibulae, an expansive aboral ganglion (450 x 100 mum) was present in the larval mid region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Given that the larval 5HT-NS expresses synaptotagmin (anti-synaptotagmin antibodypositive nervous system, Syn-NS) (Katow et al, 2009), the distribution of the 5HT-NS in larvae was examined using an antisynaptotagmin antibody. The spatial distribution patterns of the Syn-NS and DAGs were examined in 34dpf plutei by immunohistochemistry, which revealed that the Syn-NS and DAGs showed distinctly separate patterns of distribution (Fig.4A-C).…”
Section: H Katow and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the larval 5HT-NS expresses synaptotagmin (anti-synaptotagmin antibodypositive nervous system, Syn-NS) (Katow et al, 2009), the distribution of the 5HT-NS in larvae was examined using an antisynaptotagmin antibody. The spatial distribution patterns of the Syn-NS and DAGs were examined in 34dpf plutei by immunohistochemistry, which revealed that the Syn-NS and DAGs showed distinctly separate patterns of distribution (Fig.4A-C).…”
Section: H Katow and Othersmentioning
confidence: 99%
“…In sea urchin embryos, motile cilia are evident from the blastula stage, and rotatory movement by embryos can be observed in the fertilization envelope. Serotonin plays a role in the regulation of the beating of larval cilia (Yaguchi and Katow, 2003;Katow et al, 2009). However, its role in the regulation of the cilia of blastulae is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in recent years, some aspects of echinoderm neurobiology have received particular attention. One of these is the larval embryonic system and its evolutionary relationship to those of other deuterostomes, including chordates (Bishop and Burke 2007; Byrne and Cisternas 2002; Chee and Byrne 1999; Dupont et al 2009; Hirokawa et al 2008; Katow et al 2009; Murabe et al 2008; Nakano et al 2006; Yaguchi et al 2006). Many of these larval studies were made possible by the development of an antibody that recognizes echinoderm synaptotagmin (Burke et al 2006b); thus highlighting the importance of having markers for identifying nervous tissue components.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, adult sea urchins have been regarded as having no brain (Peterson et al, 2000). On the other hand, the larval nervous system (LNS) retains the bilateral body plan of deuterostomes, with an apical ganglion that contains dozens of synaptotagmin-expressing serotonergic and non-serotonergic neurons on the dorso-frontal side of the larval mouth (Yaguchi and Katow, 2003; Katow et al, 2009; Elia et al, 2009; Hoekstra et al, 2012). The ontogenetic analysis of LNS has been fairly well documented, particularly for the serotonergic NS.…”
Section: Introductionmentioning
confidence: 99%
“…The ontogenetic analysis of LNS has been fairly well documented, particularly for the serotonergic NS. The ANS is connected to the LNS at a node near the adult rudiment by synaptotagmin-expressing nerves (Katow et al, 2009). The serotonergic NS is present at a trace level in the adult rudiment of Holopneustes purpurascens for a short period during the early stage of metamorphosis, but is absent in adults (Katow et al, 2009).…”
Section: Introductionmentioning
confidence: 99%